Pengelolaan 9 Pilar Karakter dari Indonesia Heritage Foundation Pada Kelompok B di TK Muslimat NU Masyithoh 19 “ANNISA” Jenggot Kota Pekalongan - Mila Aulia Nur Komariyah; Nan Rahmaminawati; Nurul Afrianti (UNISBA Press, 2022)
Abstract. Muslimat NU Masyithoh Kindergarten 19 “ANNISA” Beard Pekalongan City has a program to implement the 9 pillars of character education from the Indonesia Heritage Foundation. There are three character streams that are introduced to children, namely moral knowing (knowledge of character), moral feeling (feeling the impact of character), moral action (making character values ​​into habituation). Based on this, the problems in this research are formulated as follows: How are the principals and teachers planning the implementation of the 9 pillars of character in TK Muslimat NU Masyithoh 19